National Movement Games Transition Methodology - Utepbergenov Genjabay Kutlimiratovich (International Journal on Orange Technologies, 2021)
As the first President of the Republic IA Karimov said: Wrestlers, who are the heroes and defenders of our time, have always cared for and nurtured children. Today, national sports are being revived everywhere. The people of Uzbekistan are showing courage in the sports community. Many wise men, heroes and warriors have grown up among our wise people. As our children grow up to be physically strong and mature, children's folklore games, which are on a par with traditional children's medicine, are bright and vibrant in the future. The roots of Uzbek children's folklore games go back to ancient times. that is, it dates back to the millennia.